Pengaruh Motivasi Kerja dan Kepemimpinan terhadap Kinerja Pegawai di Dinas Koperasi Usaha Kecil dan Menengah Kabupaten Musi Rawas - Gregorius Wartono; Suyadi Suyadi (Journal of Management and Bussines (JOMB), 2020)
This study aims to determine the effect of motivation and work environment on the Employee Performance of the Musi Rawas Cooperative Office for Small and Medium Enterprises. A sample of 44 employees was selected by the Saturated Sampling Method. The results showed that the calculated Fcount (18,566) was greater than the Ftable 2,810. Conclusion, work motivation and leadership simultaneously have a significant effect on the performance of employees in the Department of Cooperatives of Small and Medium Enterprises in Musi Rawas Regency. Keywords: Motivation, Leadership, Performance